Alcune note sociologiche (ma non solo) sulla mentalità dei genovesi - Gianfranco Bettin Lattes (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
Mentality, an ambivalent analytical category, is in fact a relevant resource from a cultural point of view due to its reflections on the concrete behaviors of both the individual and a community. The essay attempts to reflect sociologically on the mentality with reference to a specific case study: the Genoese people. Here focus only on three interdependent aspects, that traditionally contribute to the configuration of the Genoese mentality: avarice, grumbling and the fear of the new expressed in the lexicon of the maniman. Some banal stereotypes are thus dismantled. This preliminary exploration adopts an interdisciplinary methodology based on a plurality of sources and data in the hope of further insights.